PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) TERHADAP KETERAMPILAN MENULIS KARANGAN EKSPOSISI SISWA KELAS X SMA NEGERI 1 SUNGAI LIMAU - Cici Ramayani (JURNAL PENDIDIKAN ROKANIA, 2016)
This article purposed to look the influence of problem based learning model to the students’ exposition essay writing skill grade X in SMAN 1 Sungai Limau. The data in this research is the result of thbe final score (posttest) of students’ exposition essay writing skill by using problem based learning model. The hipotesis was tested by using the t-test formula test. The results of this study are is as follows (1) essay writing skills pretest results eksposition is 60,52; (2) the results posttest writing skills essay exposition is 75,46; (3) based on the test results of t-test conclude that influence the use of models to accuse problem based learning writing skills essay exposition student of class X SMAN 1 Sungai Limau